71‐2: Novel Optical Image Sensor Array Using LTPS‐TFT Backplane Technology as Fingerprint Recognition. Issue 1 (29th May 2019) - Liu, Bozhi; Shi, Xiaoqi; Cai, Shoujin; Cai, Xuanxian; Lan, Xuexin; Chen, Guozhao; Li, Junyi
Abstract : A novel photo sensor by LTPS TFT backplane technology is developed, which amorphous silicon (a‐Si) layer stacks on poly silicon (p‐Si) layer to form a vertical hybrid poly and amorphous silicon PIN photo diode (HPAS‐PIN). This photo diode shows good photosensitivity as traditional a‐Si photo sensor. An optical fingerprint sensor array is realized based on the novel HPAS‐PIN photo diode and successfully capturing fingerprint image.